2008
DOI: 10.1007/s11113-007-9058-1
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Succession in the US Housing Market: New Houses, the Baby Boom, and Income Stratification

Abstract: Housing, Income stratification, Cohort analysis, Baby boom,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…We found that affluent households are significantly more likely than middle‐income households to be owner occupiers, and among all households and owner‐occupier households, affluent households are more likely than middle‐income households to live in larger homes and more recently built homes. Among owner occupiers, the average housing values for higher‐income groups are significantly higher than the middle‐income group, which is consistent with Dwyer's research in the U.S. (2008, 2009). Of particular note is that for the average size of homes and the average housing value, there is a significant increase in these values between households in the 80th to 90th and 90th to 100th percentile income groups, relative to middle‐income households, revealing that extremely affluent households have significantly better homes even better than other affluent groups.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We found that affluent households are significantly more likely than middle‐income households to be owner occupiers, and among all households and owner‐occupier households, affluent households are more likely than middle‐income households to live in larger homes and more recently built homes. Among owner occupiers, the average housing values for higher‐income groups are significantly higher than the middle‐income group, which is consistent with Dwyer's research in the U.S. (2008, 2009). Of particular note is that for the average size of homes and the average housing value, there is a significant increase in these values between households in the 80th to 90th and 90th to 100th percentile income groups, relative to middle‐income households, revealing that extremely affluent households have significantly better homes even better than other affluent groups.…”
Section: Discussionsupporting
confidence: 87%
“…A final limitation with this paper is that it only studies income-based disparities in housing outcomes in just one country. While our results are similar to findings from U.S. based research (Dwyer 2008(Dwyer , 2009, expanding the examination of such differences to a larger number of countries would be beneficial in assessing whether middle-income households are disadvantaged in a broader range of countries, particularly at varying levels of income and wealth inequality and where the middle-income segment of the population is expanding (Kharas 2017).…”
Section: Discussionsupporting
confidence: 79%
“…Critiques of quantitative approaches to understanding population change have questioned the assumptions researchers make when assigning causation to observed relationships in the data and the spatial homogeneity of observed trends. However, those limitations acknowledged, quantitative data can provide useful and appropriate information if the research question takes into account the limitations of the research approach (see for example, Dwyer, 2008).…”
Section: Constructing Ageing Populations: Making the Case For A Mixedmentioning
confidence: 99%